The Impact of Knowledge Management, Learning Organization, and Educations Organization on Organization Performance: A Case in Brawijaya University - Giuma Omar Al Ahmar; Ainur Rofiq; Djumilah Zain Hadiwodjojo (APMBA (Asia Pacific Management and Business Application), 2014)
This study aims to investigate the impact of knowledge management, learning organization, and education organization on organization performance at University of Brawijaya. The Quantitative   method was applied to conduct this study. A questionnaire of four dimensions with 41 items was distributed to the sample target of 140 administrative employees at University of Brawijaya. Structural Equation modeling was used to analyze the data. The results show that there are positive relationships between knowledge management and education organization, learning organization and education organization, as well as education organization and learning organization. And no significant negative effect onthe education organization, where the stronger knowledge management, knowledge management directly and no significant negative effect on organization performance, the learning organization directly and not significant positive effect on organization performance, and that the learning organization directly and not significant positive effect on organization performance, in which the stronger learning organization tend to improve organization performance.